Phototherapy induced hypocalcemia in neonatal hyperbilirubinemia and correlation of hypocalcemia with the duration of phototherapy - Basnet, Subash; Gauchan, Eva; Bhatta, Mukesh; Thapa, Rubi (International Journal of Contemporary Pediatrics, 2022)
Background: Neonatal hyperbilirubinemia is common morbidity in the first week of life. Approximately 5-10% of them requires intervention like phototherapy and even exchange transfusion. Phototherapy has various adverse effects and hypocalcemia is one of them. Thus assessment of serum calcium levels after phototherapy should be done in neonates with jaundice. Background: Neonatal hyperbilirubinemia is common morbidity in the 1st week of life. Approximately 5-10% of them requires intervention like phototherapy and even exchange transfusion. Phototherapy has various adverse effects and hypocalcemia is one of them. Thus, assessment of serum calcium levels after phototherapy should be done in neonates with jaundice. Objectives were to study prevalence of hypocalcemia in neonates with unconjugated hyperbilirubinemia receiving phototherapy and to observe association of hypocalcemia with duration of phototherapy. Methods: This was a prospective observational study conducted over a period of 18 months among 75 neonates (both term and preterm) in the neonatal intensive care unit of Manipal teaching hospital, Pokhara. Total serum calcium level was measured at 0 hours (control), 12 hours, and after 48 hours and data were analyzed using statistical package for social sciences version 21. Results: Hypocalcemia was found only in term neonates (n=8; 14%). Of those who had hypocalcemia, the majority experienced hypocalcemia after 48 hours of starting phototherapy. The mean difference of total serum calcium level before and after phototherapy in preterm and term neonates was found to be statistically significant. Hypocalcemia was not found to be associated with the duration of phototherapy. Conclusions: The present study concludes that though there is a reduction in the serum calcium with increased duration of phototherapy, however, it does not fall to the level where treatment is required. Hence it is not recommended to monitor serum calcium levels in neonates receiving phototherapy.